2017
DOI: 10.1063/1.4976133
|View full text |Cite
|
Sign up to set email alerts
|

Water dissociation on Ni(100), Ni(110), and Ni(111) surfaces: Reaction path approach to mode selectivity

Abstract: A comparative study of mode-selectivity of water dissociation on Ni(100), Ni(110), and Ni(111) surfaces is performed at the same level of theory using a fully quantum approach based on the reaction path Hamiltonian. Calculations show that the barrier to water dissociation on the Ni(110) surface is significantly lower compared to its close-packed counterparts. Transition states for this reaction on all three surfaces involve the elongation of one of the O-H bonds. A significant decrease in the symmetric stretch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 78 publications
3
19
0
Order By: Relevance
“…c) Email: g.j.kroes@chem.leidenuniv.nl more and more degrees of freedom (DOFs) and details in the potential energy surface (PES). 3,4,[7][8][9][10][11]15,[17][18][19][20][21][22][23][24]26,30 The dissociation of water on metal surfaces is a late barrier process 3,4,15 which is greatly promoted by vibrational energy in the molecule, 3,4,20,21 and it exhibits large mode 9,10 and bond 19 specificity in agreement with Polanyi's rule. 31 This is also in agreement with results of the sudden vector projection (SVP) model 5,6 which predicts large couplings between the vibrational modes of the reactant and the reaction coordinate at the transition state.…”
Section: Introductionsupporting
confidence: 53%
“…c) Email: g.j.kroes@chem.leidenuniv.nl more and more degrees of freedom (DOFs) and details in the potential energy surface (PES). 3,4,[7][8][9][10][11]15,[17][18][19][20][21][22][23][24]26,30 The dissociation of water on metal surfaces is a late barrier process 3,4,15 which is greatly promoted by vibrational energy in the molecule, 3,4,20,21 and it exhibits large mode 9,10 and bond 19 specificity in agreement with Polanyi's rule. 31 This is also in agreement with results of the sudden vector projection (SVP) model 5,6 which predicts large couplings between the vibrational modes of the reactant and the reaction coordinate at the transition state.…”
Section: Introductionsupporting
confidence: 53%
“…In complementarity with the EC simulations, physically-based modeling is an efficient tool to propose and check the relevance of reaction mechanisms. In this frame, several authors have studied the steam and hydrogen interaction with Ni/YSZ using Density Functional Theory (DFT) to determine the most energetically favorable configuration [44][45][46][47][48][49][50][51][52][53][54][55][56]. These theoretical investigations showed that the interaction of hydrogen with the Ni/YSZ system results in dissociative adsorption of H 2 on the Ni surface [44,49,50,54], whereas steam molecules can be adsorbed on both surfaces.…”
Section: (1a) (1b)mentioning
confidence: 99%
“…101,[143][144][145][146][147][148][149][150][151] Researchers are also starting to use meta-GGA (mGGA) DFs. 151,152 Goals of these calculations include validating models, 61,62,65,73,74,76,86,89,98,100,102,105,106,123,145,153 analyzing features of the reaction mechanism, 21,51,53,58,[64][65][66][69][70][71][72]75,77,[79][80][81][82]87,[90][91][92][93][94]…”
Section: Introductionmentioning
confidence: 99%